ISOLASI DAN IDENTIFIKASI VIRUS AVIAN INFLUENZA PADA BERBAGAI SPESIES UNGGAS SECARA SEROLOGIS DAN MOLEKULER (Isolation and Identification of Avian Influenza in Different Species of Poultry by Means of Serological and Molecular Methods) - Teuku Zahrial Helmi; Charles Rangga Tabbu; Wayan Tunas Artama; Aris Haryanto; Muhammad Isa (Universitas Syiah Kuala, 2016)
The purpose of this research was to identify avian influenza (AI) virus using serological and molecular methods on poultry which suspected as AI infected in Aceh province. This study used 37 samples of tracheal and cloacal swabs and organs from various species of poultry that were collected from several districts/cities in Aceh. Samples were collected and put into transport media and stored at 4° C before sending to the laboratory. Samples were inoculated in specific pathogen-free of embryonated chicken egg with the age of 9-11 days for further serological and molecular examination. From 37 samples which infected to embryonated chicken egg then followed by hemagglutinin agglutination test/hemagglutinin inhibition revealed that 7 samples were positively infected with AI virus. The amplification result of specific matrix gene primer was followed by electrophoresis on 2% agarose gel which were obtained in the form of a deoxyribonucleic acid (DNA) band at 276 bp for matrix gene and 1.725 bp for H5 gene for all isolates test. In conclusion, the virus which caused the death of various types of poultry in Aceh province is avian influenza A virus subtype H5.Key words: avian influenza virus, H5N1, serologic, matrix, heamaglutinin